The study of alkali-metal localization in zeolite matrix using CO as probe molecule - Frolich, Karel (Univerzita Pardubice, 2009)
The subject of this doctoral thesis was the study of behaviour of small molecules trapped in confined space of zeolitic channels and integracting with cations coordinated to zeolite.
The study of alkali-metal localization in zeolite matrix using CO as probe molecule
Keywords: zeolity; alkalický kov; oxid uhelnatý; FTIR; zeolite; alkali-metal; carbon monoxide